« I could not do without medieval Christianity » : transmission et mysticisme dans The Hours de Burne-Jones - Nadezda Seliverstova (Cahiers Victoriens et Edouardiens)
This article examines the question of transmission in the art of Edward Burne-Jones and precisely in his painting The Hours. The work refers to the art of the past and, more specifically, to the concept of unity revealed by the relational configurations between the figures in Byzantine images. Burne-Jones’s figures are compared with those in Andrei Rublev’s icon of the Trinity. This analysis makes a comparative study of Byzantine art and Pre-Raphaelite painting, and examines the place of Orthodox art in Burne-Jones’s painting.